End-of-life care for people with severe mental illness: the MENLOC evidence synthesis - Ben Hannigan; Deborah Edwards; Sally Anstey; Michael Coffey; Paul Gill; Mala Mann; Alan Meudell (NIHR Journals Library, 2022)
Background: People with severe mental illness have significant comorbidities and a reduced life expectancy. This project answered the following question: what evidence is there relating to the organisation, provision and receipt of care for people with severe mental illness who have an additional diagnosis of advanced incurable cancer and/or end-stage lung, heart, renal or liver failure and who are likely to die within the next 12 months? Objectives: The objectives were to locate, appraise and synthesise relevant research; to locate and synthesise policy, guidance, case reports and other grey and non-research literature; to produce outputs with clear implications for service commissioning, organisation and provision; and to make recommendations for future research. Review methods: This systematic review and narrative synthesis followed international standards and was informed by an advisory group that included people with experience of mental health and end-of-life services. Database searches were supplemented with searches for grey and non-research literature. Relevance and quality were assessed, and data were extracted prior to narrative synthesis. Confidence in synthesised research findings was assessed using the Grading of Recommendations, Assessment, Development and Evaluation and the Confidence in the Evidence from Reviews of Qualitative Research approaches. Results: One hundred and four publications were included in two syntheses: 34 research publications, 42 case studies and 28 non-research items. No research was excluded because of poor quality. Research, policy and guidance were synthesised using four themes: structure of the system, professional issues, contexts of care and living with severe mental illness. Case studies were synthesised using five themes: diagnostic delay and overshadowing, decisional capacity and dilemmas, medical futility, individuals and their networks, and care provision. Conclusions: A high degree of confidence applied to 10 of the 52 Grading of Recommendations, Assessment, Development and Evaluation and Confidence in the Evidence from Reviews of Qualitative Research summary statements. Drawing on these statements, policy, services and practice implications are as follows: formal and informal partnership opportunities should be taken across the whole system, and ways need to be found to support people to die where they choose; staff caring for people with severe mental illness at the end of life need education, support and supervision; services for people with severe mental illness at the end of life necessitate a team approach, including advocacy; and the timely provision of palliative care requires proactive physical health care for people with severe mental illness. Research recommendations are as follows: patient- and family-facing studies are needed to establish the factors helping and hindering care in the UK context; and studies are needed that co-produce and evaluate new ways of providing and organising end-of-life care for people with severe mental illness, including people who are structurally disadvantaged. Limitations: Only English-language items were included, and a meta-analysis could not be performed. Future work: Future research co-producing and evaluating care in this area is planned. Study registration: This study is registered as PROSPERO CRD42018108988. Funding: This project was funded by the National Institute for Health Research (NIHR) Health and Social Care Delivery Research programme and will be published in full in Health and Social Care Delivery Research; Vol. 10, No. 4. See the NIHR Journals Library website for further project information.